DETERMINASI NILAI PERUSAHAAN: UKURAN PERUSAHAAN, LEVERAGE DAN PROFITABILITAS PADA PERUSAHAAN SEKTOR INDUSTRI KONSUMSI PRIMER YANG TERDAFTAR DI BEI TAHUN 2020 - 2022 - Gunawan, Felicia Septiana; Nuswandari, Cahyani (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This inquiry aims to comprehend and evaluate the impact of corporate scale, leverage, and profitability on the valuation of entities in the primary consumption industry sector listed on the Indonesia Stock Exchange (ISE) from 2020 to 2022. The population for this investigation comprises 369 firms in the primary consumption industry sector registered on the BEI during the specified period. A sample of 291 firms was selected through purposive sampling for analysis. Multiple linear regression analysis was utilized as the method for data examination in this research. Findings reveal that corporate valuation correlates positively with leverage and profitability, whereas corporate scale exerts a negative influence.